Numbers and Potential Causes of Medication Error in Inpatient Service of Rumah Sakit Islam Malang - Arundina, Arsy; Widyaningrum, Kurnia (Jurnal Kedokteran Brawijaya, 2020)
Medication errors, ranging from prescription to administration errors, are still problems of patient safety with an average error rate of 8% - 10% and can cause severe morbidity, prolonged length of stay (LOS) in a hospital, unnecessary diagnostic tests and care, and mortality. The objective of this study is to describe the number of medication errors and their potential causes according to the perceptions of health personnel. The study was carried out by questionnaires, interviews, and data exploration on prescriptions made before the observation period and new prescriptions made during the observation period. The priority determination of the solutions was carried out using Capability, Assessibility, Readiness, and Leverage method (CARL) and discussions with related units. The priority root factors that caused medication errors in the inpatient pharmacy at RSI Malang were high workloads and high turnover of inpatient pharmacist, incomplete prescription identity, illegible doctor's writing, and lack of training for the pharmacist. The priority outcome of the alternative solutions to overcome the medication errors in inpatient pharmacist is to regularly conduct training or knowledge refreshing for the inpatient pharmacist at RSI Malang and the implementation of e-prescription.